Evaluation of Fish Cultivation Water Quality in Aquaponic Systems with Different Aeration Systems - Kosasih, Henry Putra; Zahidah, Zahidah; Subhan, Ujang; Andriani, Yuli (Jurnal Perikanan dan Kelautan, 2025)
Aquaponics is a sustainable aquaculture technology that integrates a recirculation aquaculture system with plant cultivation in one system. The aquaponic system can be a solution that can be used as an intensive fish farming system and increase fish farming production. However, intensive cultivation will cause dissolved oxygen concentration to decrease rapidly. It will affect the water's quality, so an aeration system is needed to maintain the balance of dissolved oxygen in the water. The difference in the use of aeration systems in aquaponic systems will certainly provide different water quality results. So, this study aims to determine the type of aeration system most effective for cultivation activities in the aquaponic system. The method used in this study is a descriptive exploration of various literature and research results that have been published, both from books, national journals, and international journals. Based on a comparison of the results of previous studies, it can be concluded that aeration technology with microbubble sizes such as MNB and FBs can increase oxygen higher and more stable than conventional and venturi aeration technologies. The application of MNB and FBs aeration technology can produce water quality with dissolved oxygen concentration >7 mg/L, reduce ammonia concentration to <0.01 mg/L, nitrate concentration to <0.6 mg/L, and phosphate concentration <0.3 mg/L, as well as reducing total solids to 16% and volatile solids to 32%.